Ancient to recent-past runoff harvesting agriculture in the hyper-arid Arava Valley: OSL dating and insights. (June 2021) - Stavi, Ilan; Ragolsky, Gidon; Haiman, Mordechai; Porat, Naomi
Runoff harvesting agriculture was prevalent in ancient times across the southern Levant. In modern Israel, remnants of this agricultural adaptation strategy are widespread mostly in the semi-arid and arid Negev. Extensive literature has thoroughly described the farming systems of this region. However, runoff agriculture in the dryer, hyper-arid regions of the Arava Valley and southern Negev (excluding the Uvda Valley), has scarcely been researched. A recent study revealed remnants of simple stone terraces in several wadis (ephemeral stream channels) throughout the central Arava Valley that have not yet been dated. The objective of this study was to use the Optically Stimulated Luminescence (OSL) method to date sediments trapped in the stone terraces. The results revealed dominance of terraces dated to the Ottoman period (1516–1917 CE). Few samples were dated to the earlier Late Islamic period (1099–1516 CE) or Byzantine period (324–638 CE), and to the later, modern period of the mid-20th century. Generally, these periods coincide with relatively moister regional climatic conditions, which prevailed in the 4th, 11th–12th, and late 19th centuries CE. Yet, our findings also concur with periods of effective governance by central administrations. Therefore, results of this study fit the concept that runoff agriculture practiced in peripheral areas in ancient to recent-past times was co-determined by climatic settings and geo-political conditions, which enabled human inhabitation in these regions.